2016
DOI: 10.3847/0004-637x/831/1/99
|View full text |Cite
|
Sign up to set email alerts
|

On Understanding the Nature of Collisions of Coronal Mass Ejections Observed by Stereo

Abstract: Our study attempts to understand the collision characteristics of two coronal mass ejections (CMEs) launched successively from the Sun on 2013 October 25. The estimated kinematics, from three-dimensional (3D) reconstruction techniques applied to observations of CMEs by SECCHI/Coronagraphic (COR) and Heliospheric Imagers (HIs), reveal their collision around 37 R ⊙ from the Sun. In the analysis, we take into account the propagation and expansion speeds, impact direction, angular size as well as the masses of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…We made several independent mass measurements for this event and found that the values are within 20% of the measured ones. Further, the role of the uncertainty in the mass estimation has been studied to understand the variation in the coefficient of restitution which has been found to be negligible in deciding the nature of the collision (Shen et al, 2012;Mishra, Wang, and Srivastava, 2016). This is expected as our approach constrains the momentum conservation while modifying the observed post-collision speeds .…”
Section: Momentum Energy Exchange and Nature Of The Collisionmentioning
confidence: 99%
See 2 more Smart Citations
“…We made several independent mass measurements for this event and found that the values are within 20% of the measured ones. Further, the role of the uncertainty in the mass estimation has been studied to understand the variation in the coefficient of restitution which has been found to be negligible in deciding the nature of the collision (Shen et al, 2012;Mishra, Wang, and Srivastava, 2016). This is expected as our approach constrains the momentum conservation while modifying the observed post-collision speeds .…”
Section: Momentum Energy Exchange and Nature Of The Collisionmentioning
confidence: 99%
“…We constructed the time-elongation maps, conventionally called J-maps, (Sheeley et al, 2008;Davies et al, 2009) using the running difference images of HI-1 and HI-2. The details of the procedure to construct the J-maps and to derive the distance from the measured elongation angles have been described in Mishra, Srivastava, and Chakrabarty (2015); Mishra, Wang, and Srivastava (2016). These J-maps reveal the kinematic evolution of these CMEs and are shown in Figure 3.…”
Section: D Reconstruction Of Interacting Cmes In Hi Fovmentioning
confidence: 99%
See 1 more Smart Citation
“…This largely stimulated the observational and numerical studies in this area (e.g. Gopalswamy et al, 2009;Xiong, Zheng, and Wang, 2009;Temmer et al, , 2014Shen et al, 2012a;Liu et al, , 2014Martínez-Oliveros et al, 2012;Webb et al, 2013;Shen et al, 2011Shen et al, , 2012bShen et al, , 2013Shen et al, , 2016Mishra and Srivastava, 2014;Mishra, Srivastava, and Chakrabarty, 2015;Mishra, Srivastava, and Singh, 2015;Mishra, Wang, and Srivastava, 2016;Shanmugaraju et al, 2014;Colaninno and Vourlidas, 2015). A comprehensive review about the interaction of successive CMEs and consequences in particle acceleration and geoeffectiveness by Lugaz et al (2017) can be found in the Topical Collection called Earth-affecting Solar Transients.…”
Section: Introductionmentioning
confidence: 99%
“…their speeds and propagation directions, and hence influence the effects they have on space weather. The current knowledge about the nature of the CME collision, which we discuss in Section 2, may be used to predict their post-collision kinematics and hence their arrival time (Mishra, Wang, and Srivastava, 2016).…”
Section: Introductionmentioning
confidence: 99%